Pemanfaatan Terbitan Pemerintah di Kantor DPRD Sumatera Barat - Hayati, Rahmah; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper discuss about the beneficial of government publication at DPRD West Sumatera. This study were purpose to describe: (1) the beneficial of government publication within the office of DPRD West Sumatera; (2) the constraints which faced in process of beneficial of government publication at the office of DPRD West Sumatera. The data were collected by direct monitoring and interview with Kabag and Kasubag of the office ofÂ  DPRD West Sumatera. The analyzing of data by descriptive way. Based on the analyzing of data, that can concluded the things such as. First, the beneficial of government publication at the office of DPRD West Sumatera was unfulfill resembled. Second, the constrain which faced in process of beneficial of government publication at the office of DPRD West Sumatera; (1) the collection of government publication is not on good arrangement yet; (2) the source of human power (SDM) which is less; (3) the responsibility of librarian, and (4) there is no input of data of government publication to computer. Keywords: government publication